Prospecção tecnológica de óleos essenciais de Schinus terebinthifolius e desenvolvimento de um creme vaginal à base de Ocimum basilicum para tratamento de candidíase - Almeida, Mônica Batista de (2013)
Vaginal candidiasis is a disease with high prevalence in adult women. This study aimed to : ( i ) assess the antiCandida activity of essential oil ( EO ) of S. terebinthifolius front lines of cases of recurrent vaginal candidiasis ; ( II ) produce a antiCandida vaginal cream from OE O. basilicum and evaluate the technological process and this cream antiCandida activity in vitro . The major compounds of OE leaves and dried fruits of S. Terebinthifolius were, respectively, the (+) - camphene (20.1%) and R- ? - pinene (22.1%). In terms of minimum inhibitory concentration (MIC ) and minimum fungicidal , OE Fruit S. terebinthifolius showed bands between 25-200 mg / ml , demonstrating activity against C. parapsilosis ( ATCC 22019 ) and a clinical strain , C. albicans (ATCC 18804) and C. glabrata (ATCC 2001) , not being active on these clinical isolates. Regarding OE leaves, no significant action was observed. The OE dried fruit showed fungistatic , however , no fungicide both OE action, in contrast, leaves and fresh fruits showed antiCandida activity, unless the standard strain of C. glabatra the essential oil from fresh fruits . The major compound of OE O. basilicum (Maria - Bonita) was linalol (72.08%). MIC values ranged between this SO 0.78 to 1.56 mg / ml. Before its antifungal action, was produced a vaginal cream. The samples were stored in these distinct conditions: controlled, refrigerator and oven temperature. In controlled and cooler temperatures, no changes in the formula, however, samples at 45 ° C showed slight changes in texture from the 15th day. It can be concluded that the EO of dried leaves and fruits of S.terebinthifolius Raddi not have antiCandida activity, however, the EO extracted from fresh material Botanical demonstrate such activity . The O. basilicum presents antiCandida action. Tests for antimicrobial activity of vaginal cream in its various concentrations showed satisfactory results compared to a synthetic antifungal.Keywords: Vaginal candidiasis, essential oils, Candida spp., Schinus terebinthifolius Raddi, Ocimum basilicum, vaginal cream, anti-candida.